Skazki - Chukovskiĭ, Korneĭ, 1882-1969 (V podarok malysham., 2010)
Collection of seven humorous stories in verse for children, including "Doctor Aibolit", "Barmalei", "Telephone", "Wash 'em clean", "Little fly so sprightly", "Cockroach", and "Fedorino mountain".